Representation of Reward Feedback in Primate Auditory Cortex - Brosch, Michael; Selezneva, Elena; Scheich, Henning (Frontiers in Systems Neuroscience, 2011)
It is well established that auditory cortex is plastic on different time scales and that this plasticity is driven by the reinforcement that is used to motivate subjects to learn or to perform an auditory task. Motivated by these findings, we study in detail properties of neuronal firing in auditory cortex that is related to reward feedback. We recorded from the auditory cortex of two monkeys while they were performing an auditory categorization task. Monkeys listened to a sequence of tones and had to signal when the frequency of adjacent tones stepped in downward direction, irrespective of the tone frequency and step size. Correct identifications were rewarded with either a large or a small amount of water. The size of reward depended on the monkeys' performance in the previous trial: it was large after a correct trial and small after an incorrect trial. The rewards served to maintain task performance. During task performance we found three successive periods of neuronal firing in auditory cortex that reflected (1) the reward expectancy for each trial, (2) the reward size received and (3) the mismatch between the expected and delivered reward. These results, together with control experiments suggest that auditory cortex receives reward feedback that could be used to adapt auditory cortex to task requirements. Additionally, the results presented here extend previous observations of non-auditory roles of auditory cortex and shows that auditory cortex is even more cognitively influenced than lately recognized.